2017
DOI: 10.1080/14781700.2017.1285247
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical, methodological and terminological issues regarding indirect translation: An overview

Abstract: The practice of indirect translation (ITr), here understood as a translation of a translation (see Gambier 1994, 413; 2003, 57), has a long-standing history (e.g. the Bible, I Ching, Shakespeare translation or the activity of the so-called Toledo School), widespread use in various areas of today's society (e.g. audiovisual, computer-assisted and literary translation, localization) and, arguably, a promising future (e.g. due to globalization and the increasingly high number of working languages in international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 44 publications
1
44
0
5
Order By: Relevance
“…[32], [33], has opinion that "relay translation is the translation of translated text (either spoken or written) into a third language". Meanwhile, [1] states that "any translation mediated by another translation".From those definitions, we may concluded that a relay translation is a translation of a translation; a double translation which is involved three languages differs.…”
Section: Literature Review 21 Relay Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…[32], [33], has opinion that "relay translation is the translation of translated text (either spoken or written) into a third language". Meanwhile, [1] states that "any translation mediated by another translation".From those definitions, we may concluded that a relay translation is a translation of a translation; a double translation which is involved three languages differs.…”
Section: Literature Review 21 Relay Translationmentioning
confidence: 99%
“…Meanwhile, [38] call it as second hand translation. This following experts deals to call it as relay translation [2], [3], [32], [26], [1], and [33]. "mediated translation" [24], "double translation" [5], and "retranslation" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect translation has only recently been given proper attention by translation scholars, as seen in the number of important publications relating to indirect translation in recent years (see Assis Rosa, Pięta and Maia 2017;Ivaska and Paloposki 2018;Marin-Lacarta 2017;Pięta 2014;Pięta 2017). For the most part, an indirect translation is often seen in a negative light, primarily because it is produced not from the original source text but based on an intermediary text which is a translation of the source text.…”
Section: Issues In Indirect Translationmentioning
confidence: 99%
“…A text which is not translated directly from the source text but is instead translated based on an intermediary text which is itself a translation from the source text is referred to as an indirect translation. An indirect translation, abbreviated to "ITr" by Assis Rosa, Pięta and Maia (2017), can thus be defined as "a translation of a translation" (Assis Rosa, Pięta and Maia 2017, 113) or "translation into Language C based on a translation into Language B of a source text in Language A" (Landers 2001, 34). The fact that indirect translation involves three different texts in three different languages is also underlined by Kittel and Frank (1991, 3), who define indirect translation as "the translation based on a source (or sources) which is itself a translation into a language other than the language of the original, or the target language".…”
Section: Introductionmentioning
confidence: 99%
“…W niniejszym tekście przyjmuję szeroką definicję przekładu niebezpośredniego jako "translacji translacji" (Assis Rosa, Pięta, Bueno Maia 2017: 119-121), która nie wskazuje liczby języków biorących udział w procesie przekładu, a zatem jednym z jego etapów może być przekład wewnątrzjęzykowy (por. klasyfikacja typologiczna przekładu niebezpośredniego w: Assis Rosa, Pięta, Bueno Maia 2017: 121-122 i Washbourne 2013. Takie ujęcie umożliwia włączenie w obszar rozważań zarówno translacji przygotowywanych na podstawie przekładu filologicznego na język docelowy, efektów pracy dwujęzycznych zespołów tłumaczy, która z reguły polega na przygotowaniu wstępnej wersji w języku docelowym przez użytkownika języka źródłowego i negocjowaniu przez obu tłumaczy ostatecznego kształtu tekstu w serii prze-pisań (Zaboklicka 2013), jak również wszelkich translacji kompilacyjnych, łączących na różne sposoby tłumaczenie wewnątrz-i międzyjęzykowe.…”
Section: Zły Obyczaj? Wprowadzenieunclassified